Alflutop efficacy in chronic vertebrogenous lumbar ischialgia. A double blind placebo controlled study - O S Levin; D Y Olyunin; L V Golubeva (Научно-практическая ревматология)
Objective. To assess efficacy and safety of intramuscular (im) and paravertebral (pv) alflutop injections in pts with chronic vertebrogenous lumbar ischialgia. Material and methods. 83 pts with lumbar ischialgia syndrome (44 male, 39 female) aged 31 to 56 years (mean 43,1 ±5,2 years) were included. Disease duration varied from I to 7 years (mean 3,5± 1,9 years), duration of the present exacerbation - from 1 to 4 months (mean 2.4±0,8 months). Vertebroneurologic diagnosis was made according to H. Hall criteria. Pts were randomized into 4 groups. 32 pts of group Al received im, 23 pts of group A2 - pv alflutop injections. 14 pts of group Bl and 14 pts of group B2 received im and pv placebo injections respectively. Treatment results were scored by the doctor. Pts assessed spine pain changes on visual analog scale. Quantitative assessment of verbal syndrome was performed with Waddle scale. Results. Im alflutop injections provided good or fair effect in 61%, pv - in 69% of pts (significantly better than placebo). Effect was evident during the first 2 weeks of treatment and persisted for 3 months after its termination. The best results were achieved in pts with facet syndrome, the worst - in spinal stenosis. Drug tolerability was good in both modes of administration.